2017
DOI: 10.1038/srep43402
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Plastid Sequences in Plant Mitochondria are Frequently Acquired Via Mitochondrion-to-Mitochondrion Horizontal Transfer

Abstract: Angiosperm mitochondrial genomes (mtDNA) exhibit variable quantities of alien sequences. Many of these sequences are acquired by intracellular gene transfer (IGT) from the plastid. In addition, frequent events of horizontal gene transfer (HGT) between mitochondria of different species also contribute to their expanded genomes. In contrast, alien sequences are rarely found in plastid genomes. Most of the plant-to-plant HGT events involve mitochondrion-to-mitochondrion transfers. Occasionally, foreign sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 48 publications
4
54
1
Order By: Relevance
“…The Acacia dpo has only 55% similarity at the protein level to sequences in other angiosperm mtDNAs, in agreement with a study that reported greater sequence divergence between plasmid-derived sequences than between other mitochondrial genes (Warren et al 2016). The A. ligulata mtDNA also contains 22 MTPTs encompassing 3.2% of the genome (Table 1), a similar value to that of other legume mitochondrial genomes (Gandini & Sanchez-Puerta 2017;Sloan & Wu 2014). Of these, two were previously described as foreign because they were closely related to sequences in Piperales and Salicales, respectively (Gandini & Sanchez-Puerta 2017).…”
Section: The Acacia Ligulata Mitochondrial Genome and A Comparison Tosupporting
confidence: 86%
See 2 more Smart Citations
“…The Acacia dpo has only 55% similarity at the protein level to sequences in other angiosperm mtDNAs, in agreement with a study that reported greater sequence divergence between plasmid-derived sequences than between other mitochondrial genes (Warren et al 2016). The A. ligulata mtDNA also contains 22 MTPTs encompassing 3.2% of the genome (Table 1), a similar value to that of other legume mitochondrial genomes (Gandini & Sanchez-Puerta 2017;Sloan & Wu 2014). Of these, two were previously described as foreign because they were closely related to sequences in Piperales and Salicales, respectively (Gandini & Sanchez-Puerta 2017).…”
Section: The Acacia Ligulata Mitochondrial Genome and A Comparison Tosupporting
confidence: 86%
“…The A. ligulata mtDNA also contains 22 MTPTs encompassing 3.2% of the genome (Table 1), a similar value to that of other legume mitochondrial genomes (Gandini & Sanchez-Puerta 2017;Sloan & Wu 2014). Of these, two were previously described as foreign because they were closely related to sequences in Piperales and Salicales, respectively (Gandini & Sanchez-Puerta 2017).…”
Section: The Acacia Ligulata Mitochondrial Genome and A Comparison Tomentioning
confidence: 67%
See 1 more Smart Citation
“…rpoC2 was usually found in the chloroplast genome coding for a RNA polymerase beta subunit (Shimada et al ., ) but traces of rpoC2 plastid gene in the mitochondrial genome have been already reported occasionally in mitochondrial genome of land plants (Goremykin et al ., ; Straub et al ., ). This result suggests an uncommon horizontal gene transfer from chloroplast to mitochondrial genome in Chlorophyta which was previously reported only upon land colonization (Wang et al ., ; Gandini and Sanchez‐Puerta, ).…”
Section: Resultsmentioning
confidence: 99%
“…These plastid genes were transferred into the host mitochondria via intergenomic transfer in the Tetrastigma host, and subsequently acquired horizontally by Rafflesiaceae, underscoring the importance of thorough phylogenetic and synteny analyses to discern vertically and horizontally inherited gene copies. The phenomenon of intergenomic transfer from plastid to mitochondrial genome within species followed by mitochondrial to mitochondrial HGT between species has been recently verified at a broader scale in plants (Gandini & Sanchez-Puerta, 2017). In Rafflesiaceae, some of the horizontally transferred mitochondrial genes appear derived from Cucurbitaceae and Apiaceae.…”
Section: Rafflesiaceae Are Prone To Horizontal Gene Transfermentioning
confidence: 96%